The Fe-Mg-saponite solid solution series – a hydrothermal synthesis study. (June 2014) - Baldermann, A.; Dohrmann, R.; Kaufhold, S.; Nickel, C.; Letofsky-Papst, I.; Dietzel, M.
Abstract: The boundary conditions of saponite formation are generally considered to be well known, but significant gaps in our knowledge persist in respect to the influence of solution chemistry, temperature, and reaction time on the mineralogy, structure, stability, and chemical composition of laboratory-grown ferrous saponite. In the present study, ferrous saponite and Mgsaponite were synthesized in Teflon-lined, stainless steel autoclaves at 60, 120 and 180°C, alkaline pH, reducing conditions, and initial solutions with molar Si:Fe:Mg ratios of 4:0:2, 4:1:1, 4:1.5:0.5, 4:1.75:0.25, and 4:1.82:0.18. The experimental solutions were prepared by dissolution of sodium orthosilicate (Na4 SiO4 ), iron(II)sulfate (FeSO4 ·6H2 O) and magnesium chloride salts (MgCl2 ·6H2 O with ≤ 0.005 mass% of K and Ca) in 50 mL ultrapure water that contained 0.05% sodium dithionite as the reducing agent. The precipitates obtained at two, five and seven days of reaction time were investigated by X-ray diffraction techniques, transmission electron microscopy analysis, infra-red spectroscopy, and thermo-analytical methods. The precipitates were composed mainly of trioctahedral ferrous saponite, with small admixtures of co-precipitated brucite, opal-CT, and 2-line ferrihydrite, and nontronite as the probable alteration product of ferrous saponite. The compositions of the obtained ferrous saponites were highly variable, (Na0.44−0.59 K0.00−0.05 Ca0.00−0.02 ) (Fe 2+ 0.37−2.41 Mg0.24−2.44 Fe 3+ 0.00−0.28 )Σ2.65−2.85 [(Fe 3+ 0.00−0.37 Si3.63−4.00 )O10 ](OH)2, but show similarities with naturally occurring trioctahedral Fe and Mg end members, except for the Al content. This suggests that a complete solid solution may exist in the Fe-Mg-saponite series. A conceptual reaction sequence for the formation of ferrous saponite is developed based on the experimental solution and solid compositions. Initially, at pH ≥ 10.4, brucite-type octahedral template sheets are formed, where dissolved Si-O tetrahedra are condensed. Subsequent reorganization of the octahedra and tetrahedra via multiple dissolution-precipitation processes finally results in the formation of saponite structures, together with brucite and partly amorphous silica. The extent of Fe 2+ incorporation in the octahedral template sheets via isomorphic substitution is suggested to stabilize the saponite structure, explaining (i) the abundance of saponite enriched in VI Fe 2+ at elevated Fe supply and (ii) the effect of structural Fe on controlling the net formation rates of ferrous saponite.